1982
DOI: 10.1002/ps.2780130304
|View full text |Cite
|
Sign up to set email alerts
|

Stability of pyrethroids on wheat in storage

Abstract: The four pyrethroids, permethrin, phenothrin, fenvalerate and deltamethrin were applied to wheat which was stored for 52 weeks at 25 or 35"C, and either 12 or 15% moisture content. Rates of loss were calculated from residue analyses of the wheat at five intervals during storage. Calculated half-lives (weeks) for the pyrethroids at 25°C (12% moisture) and 35°C (15 % moisture) were: permethrin 252 and 44, phenothrin 72 and 29, fenvalerate 210 and 74, and deltamethrin 114 and 35, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
7

Year Published

1982
1982
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 9 publications
1
12
0
7
Order By: Relevance
“…In contrast, pirimiphos-methyl applied at 10 mg/kg showed rapid decomposition, only 16% of the applied dose remaining after 14 weeks. Deltamethrin applied to wheat at a moisture content of 15% and stored at 358 C has been estimated to have a half-life of 35 weeks (Noble et al, 1982). However, in trials undertaken at lower temperatures, insecticide persistence was shown to improve.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, pirimiphos-methyl applied at 10 mg/kg showed rapid decomposition, only 16% of the applied dose remaining after 14 weeks. Deltamethrin applied to wheat at a moisture content of 15% and stored at 358 C has been estimated to have a half-life of 35 weeks (Noble et al, 1982). However, in trials undertaken at lower temperatures, insecticide persistence was shown to improve.…”
Section: Discussionmentioning
confidence: 98%
“…In corn treated with three different rates (0.5, 0.75, or 1 ppm) of deltamethrin, survival of T. castaneum adults was observed at all the storage periods; however, there were no progeny. The signiÞcant decline observed in our study in the efÞcacy of chlorpyrifos-methyl ϩ deltamethrin as the posttreatment period increased may be because of degradation of chlorpyrifos-methyl, which breaks down rapidly at high grain temperatures and moisture contents; residues of deltamethrin are more persistent on grains (Noble et al 1982, Arthur et al 1992, Afridi et al 2001. Subramanyam et al (2012) reported 100% T. castaneum mortality and signiÞcant reduction of progeny production on wheat treated by using 3 ppm of chlorpyrifos-methyl and 0.5 ppm of deltamethrin.…”
Section: Discussionmentioning
confidence: 69%
“…The method described is rapid and more economical than the method of Simonaitis and Cail (1977) for permethrin, and than that used by Noble et al, (1982) and Hargreaves et al, (1982) for deltamethrin, fenvalerate, permethrin, and phenothrin. Less than 40mL of solvents is required to extract and clean up a 5-g sample.…”
Section: Resultsmentioning
confidence: 95%